Energy levels determination of Zn(O, Se) thin films. (January 2023) - Abdalla, Akram; Danilson, Mati; Mikli, Valdek; Bereznev, Sergei
Abstract: Ternary Zn(O, Se) films were grown onto glass and p-type Si substrates by pulsed laser deposition at substrate temperature of 500 °C, to investigate their optical properties and energy band structure using UV–Vis and UPS spectroscopic methods. It was found that the 500 nm thick Zn(O, Se) film is nearly transparent in the visible region, with an optical band gap value of 2.93 eV. The calculated valence band is positioned at −7.60 eV below the vacuum level, and it consist of O 2p and Se 4p levels or the highest bonding sp 3 hybrid states with the hybridization of Zn 3d, O 2p and Se 4p orbitals, and also the coupling of 3d–3d electrons among different Zn 2+ cations. The findings show that the conduction band of Zn(O, Se) layers can be tuned for alignment with the conduction band of the absorbers layer which will decrease the cliff and spike barriers in the complete solar cell structures.